Seasonal bacterial profiles of Vellozia with distinct drought adaptations in the megadiverse campos rupestres - Otávio Henrique Bezerra Pinto; Bárbara Bort Biazotti; Rafael Soares Correa de Souza; Juliana Érika de Carvalho Teixeira Yassitepe; Paulo Arruda; Ricardo Augusto Dante; Isabel Rodrigues Gerhardt (Scientific Data)
Abstract Microbial communities can vary as a function of seasonal precipitation and the phenotypic characteristics of the prevailing plant species in an ecosystem. The Brazilian campos rupestres (CRs) host a unique flora adapted to harsh conditions, including severe droughts and nutrient-poor soils. Velloziaceae, a dominant angiosperm family in CRs, exhibit contrasting drought adaptive strategies, prominently desiccation tolerance and dehydration avoidance. Here, we created a comprehensive dataset of microbial composition and dynamics of bulk soil and distinct plant compartments (leaf blade, dry sheath, aerial root, and underground root) from two desiccation-tolerant and two dehydration-avoiding, non-desiccation-tolerant Vellozia species, across four seasons (beginning and end of rainy and dry seasons) through 16S rRNA gene sequencing of 374 samples. This dataset also includes 38 soil metagenomes encompassing dry and rainy seasons from both drought adaptive strategies. Exploring an overlooked aspect of CRs biology offers significant potential for understanding plant-microbial associations and adaptations to water availability in tropical regions. The genetic data and metadata support further research for hypothesis testing and cross-study comparisons.